Population Density and GastropodCerithidea quoyiiDistribution Patternin the Mangrove Forest of Sungai Cingam Village Rupat districts Bengkalis RiauProvince - Manalu, Lili Yanti; Samiaji, Joko; Tanjung, Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract             Cerithidea quoyii clam is agastropod living in mangrove ecosystem, and knownasprotein source for Rupat people. This research was conducted in July 2018.The purpose of the study was to determine the population density and distribution patterns of C. quoyii in the mangrove forest of Cingam River, Bengkalis Regency, Riau Province.The method used in this study was the survey method. The the research station was determined by purposive sampling method. The results showed that water quality parameters supported the life of C. quoyii, in which water temperatures ranged from 29 - 30°C, salinity ranged from 29-30 ppt, the pH value of the water was 7.Sediment organic matter was classified as high, ranging from 12.29 - 19.46%.The average population density between stations ranged from 1.22-4 ind/m2, the highest density was in station II and the lowest was in station III,while the average value between zones ranged from 0-5 ind/m2,the highest density is in the Lower zone and the lowest in the lower and middle zones of the intertidal zone. Keywords :Population Density, Distribution Pattern, Cerithidea quoyii